(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the adapted formats designed for audiences with visual impairments, the technological solutions currently implemented in global and local media practices, and the existing challenges and future prospects in this domain. The paper aims to identify pathways for the development of journalism based on the principles of information equity, thereby contributing to the theoretical and practical foundations of inclusive journalism.